The Blood of the Stars: Unravel the Dusk - Book 2 - Lim, Elizabeth (New York : Alfred A. Knopf, 2020)
"Maia Tamarin proved her skill as a tailor when she wove the dresses of the sun, the moon, and the stars, but it will take more than a beautiful gown to hide the darkness rising up within her in the sequel to Spin the Dawn"--
Keywords: Women tailors -- Juvenile fiction; Magic -- Juvenile fiction; Women tailors -- Fiction; Magic -- Fiction; Fantasy; Fantasy fiction